Analisis Pemahaman Mahasiswa Terhadap Penerapan Akad Wadiah di Bank Syariah Indonesia (Studi Pada Mahasiswa Prodi Perbankan Syariah Angkatan 2023 IAIN METRO) - anjani baroroh; arlita ratna dewi (Jurnal Perbankan Syariah, 2024)
Understanding is the ability a person has to be able to understand or interpret something,for example in everyday life a person can provide an explanation of information obtained from various sources in detail using his own words according to existing concepts.Understanding of Islamic banking study program students class of 2023 about products and contracts in Islamic banks, especially on wadiah contracts. The data used are primary data and secondary data, this research is descriptive qualitative using interviews as primary data. The results we obtained from this study indicate that the level of understanding in Islamic banking study program students of class 2023 is included in the percentage of understanding about the wadiah contract.The results we obtained from this study show that the level of understanding in the 2023 class of Islamic banking study program students is included in the percentage of 85.42% so that it can be categorized as very good.